Assessing performance of aging air-cooled heat exchangers using inspection and performance data - Mokhtar, A.A. (IEEE Computer Society, 2018)
This paper focused on one of the aging assets in gas processing plants which were the air-cooled heat exchangers. The heat exchangers have been operating for more than 20 years since the plant started and may have a greater risk of breakdowns. Thus, the main objective of the study was to assess the performance of the air-cooled heat exchangers and to determine the necessary actions for continued operation. Since there was no failure data, inspection data and performance data were used in this study. The performance analysis model used was based on the heat duty of the heat exchanger. The results from the analysis revealed that the critical level of percentage of tubes plugged before triggering the alarm at the compressor is 20.5. Hence, it is proposed that the safe running level is to ensure that the percentage of tubes plugged is not more than 20, else a planned replacement must be initiated. For the trip level, the results from the heat duty showed that 33 will trigger a trip at the compressor. Â© 2017 IEEE.